2022
DOI: 10.1021/acsanm.2c03167
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development of Photoresponsive Liposomes Based on Organic Photosensitizers, Au Nanoparticles, and Azobenzene Derivatives for Nanomedicine

Abstract: Photoresponsive liposomes are controlled-release liposomes modified by photoresponsive materials. They use light with high spatial and temporal precision as a means of regulation. After excitation by light at appropriate wavelengths, photoresponsive liposomes can influence the permeability of phospholipid bilayers through the photothermal or photoisomerization effect of photoresponsive materials. The photothermal effect causes the phospholipid layer to become dispersed by local heating, and the photoisomerizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 152 publications
0
7
0
Order By: Relevance
“…In fact, various strategies involving light to release bioactive substances from lipid vesicles have been developed. For more details on this topic, the reader may refer to the following reviews [93–95] . Recently, Chander et al [96] .…”
Section: Drug Release Based On Photo‐sensitive Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, various strategies involving light to release bioactive substances from lipid vesicles have been developed. For more details on this topic, the reader may refer to the following reviews [93–95] . Recently, Chander et al [96] .…”
Section: Drug Release Based On Photo‐sensitive Vesiclesmentioning
confidence: 99%
“…For more details on this topic, the reader may refer to the following reviews. [93][94][95] Recently, Chander et al [96] showed that the incorporation of 10 mol % of 18 : 0-azoPC in small unilamellar vesicles (SUVs), which they called photoactivatable long-circulating lipid nanoparticles (paLNP), leads to vesicles with similar structural integrity, drug loading capacity, and size distribution as the well-established parent long-circulating lipid nanoparticles (LNP) comprising DSPC-cholesterol vesicles (Figure 6A/B). Pulsed light irradiation switched 18 : 0-azoPC from trans-to cisconfiguration, resulting in a progressive release up to 65-70 % of the encapsulated doxorubicin drug within a time window of 24 hours.…”
Section: Drug Release Based On Photo-sensitive Vesiclesmentioning
confidence: 99%
“…Molecular machines have also been shown to control the disruption of membranes to facilitate the nonspecific release of cargo from lipid-bound compartments . Indeed, extensive research has been conducted into the development of compounds which disrupt cellular membranes for antiviral and antimicrobial activity, , as well as for targeted drug delivery. This perspective will focus on the molecular switches and motors that exploit controlled nanomechanical motion to disrupt both cellular and model membranes.…”
Section: Controlled Release Of Cargo From Lipid Bound Compartmentsmentioning
confidence: 99%
“…Liposomes are vesicles primarily composed of phospholipids, possessing many characteristics similar to biological membranes. , Due to their excellent loading capacity and biocompatibility, liposomes are widely used for the transport and targeted release of small molecule drugs. , Among various types of liposomes, , photoresponsive liposomes are particularly noteworthy. , They can alter the structural features of lipid membranes through photothermal effects or photoisomerization effects, , increasing the permeability of the vesicles. For instance, photoresponsive liposomes based on azobenzene compounds can achieve enhanced drug release through the photoinduced trans–cis isomerization of azobenzene compounds. , …”
Section: Introductionmentioning
confidence: 99%